Acquiring a new understanding of illness and agency: a narrative study of recovering from chronic fatigue syndrome - Anne Karen Bakken; Anne Marit Mengshoel; Oddgeir Synnes; Elin Bolle Strand (International Journal of Qualitative Studies on Health & Well-Being, 2023)
Background The condition known as chronic fatigue syndrome or myalgic encephalomyelitis (CFS/ME) is poorly understood. Simplified medical models tend to neglect the complexity of illness, contributing to a terrain of uncertainty, dilemmas and predicaments. However, despite pessimistic pictures of no cure and poor prognosis, some patients recover. Purpose This study’s purpose is to provide insight into people’s experiences of suffering and recovery from very severe CFS/ME and illuminate understanding of how and why changes became possible. Methods Fourteen former patients were interviewed about their experiences of returning to health. A narrative analysis was undertaken to explore participants’ experiences and understandings. We present the result through one participant’s story. Results The analysis yielded a common plotline with a distinct turning point. Participants went through a profound narrative shift, change in mindset and subsequent long-time work to actively pursue their own healing. Their narrative understandings of being helpless victims of disease were replaced by a more complex view of causality and illness and a new sense of self-agency developed. Discussion We discuss the illness narratives in relation to the disease model and its shortcomings, the different voices dominating the stories at different times in a clinically, conceptually, and emotionally challenging area.